2022
DOI: 10.3389/fgene.2022.858882
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferation of Glioblastoma Is Contributed to Kinesin Family Member 18A and Medical Data Analysis of GBM

Abstract: Background: Glioblastoma (GBM) is widely known as a classical kind of malignant tumor originating in the brain with high morbidity and mortality. Targeted therapy has shown great promise in treating glioblastoma, but more promising targets, including effective therapeutic targets, remain to be identified. 18A (KIF18A) is a microtubule-based motor protein that is dysregulated and involved in the progression of multiple human cancers. However, the possible effects of KIF18A on GBM progression are still unclear.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In addition, NGS showed a significant decrease in the gene expression of base excision repair and motor proteins. This decrease may undermine GBM cells’ ability to function normally, collaboratively reducing the viability and proliferation of GBM ( Poletto et al, 2017 ), especially given that kinesin family members, the motor proteins downregulated in the result of NGS, have been found to be connected to and even advantageous for the proliferation of GBM cells ( Wang L. B. et al, 2022 ; Wang L. et al, 2022 ). NGS has revealed several anti-cancer mechanisms for the CB treatment of GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NGS showed a significant decrease in the gene expression of base excision repair and motor proteins. This decrease may undermine GBM cells’ ability to function normally, collaboratively reducing the viability and proliferation of GBM ( Poletto et al, 2017 ), especially given that kinesin family members, the motor proteins downregulated in the result of NGS, have been found to be connected to and even advantageous for the proliferation of GBM cells ( Wang L. B. et al, 2022 ; Wang L. et al, 2022 ). NGS has revealed several anti-cancer mechanisms for the CB treatment of GBM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, KIF18 interacts with tumors to inhibit p53, exhibiting a potential regulatory role in cancer progression. Current studies have uncovered that KIF18A has a high expression in many human tumors, including CRC [29][30][31][32]. However, its functional molecular mechanisms in CRC have not been fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Stangeland et al (9) showed that KIF18A can be a potential therapeutic target for GBM. A relevant clinical study demonstrated that KIF18A expression is higher in human GBM tissues than normal tissues, and its expression is closely associated with the recurrence of GBM in patients (10). However, to the best of our knowledge, the specific mechanism of KIF18A in GBM has not been yet elucidated.…”
Section: Introductionmentioning
confidence: 99%